Economic Implications of Technological and Energy Advancement on CO2 Emission Intensity in Selected Countries - Tomić, Daniel; Đorđević, Tina; Grdić, Matea (Oeconomica Jadertina, 2022)
In the pursuit of economic prosperity, many countries have "sacrificed" the quality of their environment to achieve higher rates of economic growth. By focusing on established industrial practices that have destroyed the environment in the long run, they have harmed their own, as well as the global ecosystem. Within this context, the main challenge for a long-term sustainable economic policy is the intertwined focus on two goals - economic growth and environmental protection. The aim of this paper is to analyse the impact of the development of environmentally related technologies, renewable energy supplies, and the total primary energy supply on the intensity of CO2 emissions based on the production within five countries in the period from 1990 to 2019. The observed countries are Italy, Germany, Croatia, Brazil, and Finland. To evaluate the relationship between the observed variables a panel analysis was used, more specifically random effect models (REM) and fixed effect models (FEM). Empirical results show that the development of environmental technologies and the supply of renewable energy have a negative impact on CO2 emissions, while the total supply of primary energy has a positive impact on CO2 emissions. The results of the research suggest that environment-related technologies and renewable energy promote the issue of environmental protection, while the overall supply of primary energy actually limits the perspective of green development.